Assessing the potential of RNA-based therapeutics for a group of Lysosomal Storage Diseases with neurological involvement - Santos, Juliana Inês (2022)
During the first two decades of the 21st century, remarkable progresses have been achieved in the field of RNA-based therapeutics. From antisense RNA to RNA modification, the therapeutic potential of RNA-based technologies has nothing but increased. In our lab, we have been addressing the potential of different RNA-based drugs to either correct or ameliorate the sub-cellular phenotype of a number of severe, life-threatening diseases: the so-called Lysosomal Storage Disorders (LSDs). Among them, we are focusing our efforts on those which present with a predominant neurological phenotype, since there are virtually no approved treatments for any of them. Briefly, two major research lines are being pursued: the first relies on the design of mutation-specific approaches to correct abnormal splicing processes in LSD-related genes, whenever they underlie pathology. The second depends upon selective downregulation of genes involved in the biosynthethic cascades that give origin to the substrates that accumulate in each pathology. Here we present an overview on our results with both approaches on Sanfilippo syndrome, a sub-group of severe neurodegenerative LSDs. For the mutation-specific, splicing correction approach, we are using U1snRNA vectors to restore the splicing defect caused by the HGSNAT mutation c.234+1G>A, that leads to Sanfilippo C disease. We started by demonstrating in vitro that a modified U1snRNA vector designed to improve the definition of HGSNAT exon 2 could partially restore its normal splicing process. Now, we are evaluating its therapeutic potential in vivo, in mice expressing the human splicing defect. For the substrate reduction approach, we are using siRNAs. By acting over a specific biosynthethic cascade, siRNAs promote an overall decrease of the accumulating substrate. So far, we have already tested this approach in patients’ fibroblasts and observed a high inhibition of the target mRNAs and a decrease in storage. Overall, there are substantial differences between these two approaches but they also face common challenges and show equally promising results.